A Critical Analysis of Health Promotion Interventions in the Prevention of Noncommunicable Diseases A Systematic Review - Maria Jose R.Ximenes; Justino Brandao; Lourdes Vita; Cesaltino De Deus; Humbertu Yohanes; Jose Oqui (Public Health and Safety International Journal, 2026)
Non-communicable diseases (NCDs) have emerged as a leading global health concern that imposes a considerable economic and social burden. Although a wide range of health promotion strategies has been applied, their capacity to produce lasting behavioural change and to lower NCD prevalence remains contested. The present study sets out to critically examine various health promotion interventions for NCD prevention through a systematic review, with the aim of pinpointing the most effective strategies as well as the obstacles encountered during implementation. A systematic review design was adopted in line with the PRISMA guidelines. The literature was retrieved from electronic database such as PubMed, ScienceDirect, and Google Scholar, covering articles published over the preceding ten years. Eligible records comprised studies addressing NCD health promotion interventions in both developing and developed countries. Data were appraised through a narrative synthesis of the relevant findings. The results indicate that interventions confined to individual education achieve only limited success in sustaining long-term behavioural change. By contrast, multisectoral interventions that integrate fiscal policy (taxation), environmental modification (nudging), and digital technology (m-Health) proved markedly more effective. In developing countries the principal constraints stem from limited resources and weak community participation, whereas in developed countries the main challenge lies in addressing social disparities in access to health information.